THE HISTORY OF STUDYING PHRASEOLOGISMS IN WORLD AND UZBEK LINGUISTICS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
The study of phraseologisms occupies a central place in both world and Uzbek linguistics, as these stable word combinations reflect the cultural, historical, and cognitive heritage of nations. In world linguistics, the origins of phraseological research can be traced to European traditions, particularly the works of Charles Bally and Vinogradov, who established theoretical foundations for the classification and analysis of phraseologisms.